Work-Sharing Benefits in Canada: An Effective Employment Stabilization Policy Measure? - Gray, David (Relations industrielles / Industrial Relations, 1996)
The topic of this paper is Canada 's work-sharing program, which is a special provision of the unemployment insurance program. The time series properties of the national and regional activity leuels ofthis program between 1982 and 1992 are analyzed with the aid of a regression equation. The model estimates the relationship between global work-sharing program activity and the business cycle in search of a countercyclical pattern. Despite evidence of persistence effects in the time series behaviour of the participation levels for the conventional Ul program, which have been tied to hysteresis effects for unemployment levels, the participation levels of this program appearto behave countercyclically, as intended. Although there is some anecdotal evidence at the firm level which would suggest instances ofrepeat usage, persistence effects are not discernible at the macroeconomic level. On the other hand, despite the fact that the program is not to be used in instances of seasonal unemployment, the model does generale seasonal patterns.